Inflated Geometric Distribution to Study the Distribution of Rural Out-Migrants - Aryal, Tika Ram (Journal of the Institute of Engineering, 2011)
The aim of this paper is to apply inflated geometric distribution to study the distribution of rural out-migrants from a household. The inflated geometric distribution is found to be a reasonable approximation to describe this distribution. The estimated value of risk parameter α was found to be 0.7004229. Findings may help planners and policy makers for designing more effective and equitable rural and urban policies. Keywords: Rural Out-Migrants DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5121 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 266-268 Uploaded Date: 20 July, 2011